University EFL Students’ Perceptions of Generative AI in Academic Writing: A Qualitative Case Study in Indonesia - Mimin Aminah; Abdul Hamid Aly (AL-ISHLAH: Jurnal Pendidikan, 2026)
The integration of generative artificial intelligence (GenAI) into higher education has significantly transformed academic writing practices, particularly in English as a Foreign Language (EFL) contexts. While GenAI tools offer pedagogical benefits, they also raise concerns regarding academic integrity, authorship, and student autonomy. This study explores university students’ perceptions of GenAI in academic writing.A qualitative case study design was employed involving 12 undergraduate EFL students at an Indonesian university. Participants were purposively selected based on their prior use of AI tools. Data were collected through semi-structured interviews and focus group discussions and analyzed using Braun and Clarke’s thematic analysis framework.Four major themes emerged: (1) perceived benefits, including improved linguistic accuracy, idea generation, time efficiency, and reduced writing anxiety; (2) challenges and limitations, such as inconsistent AI output, over-reliance, and loss of personal writing voice; (3) ethical concerns, including plagiarism risks, unclear institutional policies, and ambiguity surrounding authorship; and (4) the impact on learning processes, where AI functions both as a cognitive scaffold and a potential barrier to critical thinking and independent learning.The findings indicate that GenAI plays a dual role in EFL academic writing, simultaneously enhancing and complicating students’ writing development. While it supports language proficiency and productivity, excessive dependence may hinder deeper cognitive engagement and authenticity. The study underscores the necessity of integrating AI literacy and establishing clear ethical guidelines to promote responsible use. These insights provide implications for educators, curriculum designers, and policymakers in fostering balanced and ethical AI integration in academic writing.